Synthesis and Optical Characterization of Building-Block Plasmonic Gold Nanostructures - Nguyen, Oanh Thi Tu; Le, Chi Ha; Pham, Long Duy; Nguyen, Hieu Sy; Hoang, Chung Vu (Communications in Physics, 2017)
Plasmonics, the field involves manipulating light at the nanoscale, has been being an emergent research field worldwide. Synthesizing the plasmonic gold nanostructures with controlled morphology and desired optical properties is of special importance towards specific applications in the field. Here, we report the chemical synthesis and the optical properties of various plasmonic Au nanostructures, namely Au nanoparticles (AuNPs), Au nanorods (AuNRs) and random Au nano-islands (AuNI) that are the building blocks for plasmonic research. The results show that the AuNPs exhibited a single plasmonic resonance, the AuNRs displayed two identical and separated modes of the resonance, and the random Au nano-islands presented a very broad resonance. Specifically, tailoring the anisotropy of the Au nanorods enabled extending their resonant frequencies from the visible to the near infrared ones, which is in accordance with the finite different time domain simulations.